Descriptive audit of maternal sepsis in a tertiary care centre of North India - Kumari, Archana; Suri, Jyotsna; Mittal, Pratima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Maternal sepsis is one of the leading causes of maternal mortality around the world. The aim of this study was to study the prevalence, clinical profile and fetomaternal outcome of maternal sepsis at a dedicated Obstetric critical care unit of a tertiary care centre of North India. It was retrospective study conducted in tertiary care centre in North India Methods: Women diagnosed as sepsis or septic shock at any point in pregnancy and up to 6 weeks postpartum (irrespective of the source of infection) were included in the study. Demographic, clinical, microbiological and outcome data were recorded from the case sheets of all patients admitted in obstetrical critical care unit between January to December 2016. Outcome measures: Prevalence, bacterial organism, source of infection, mode of delivery, period of gestation, maternal and fetal outcome. Results: The prevalence of maternal sepsis was 16.5/10,000 live births. The number of maternal deaths attributable to sepsis were 35, making the maternal mortality ratio due to sepsis 128/100,000 live births. 87% of the cases were unbooked. 22% presented antenatally while 58% were postpartum and 20% were postabortal. Genital tract infection was most common source of infection. E. coli was the predominant organism in 28% followed by Methicillin resistant staphylococcus aureus in 12%. The mortality from sepsis was very high (78%). 54% of cases required mechanical ventilation and around 7% had to be shifted to intensive care unit for advanced life support and care. Sepsis was associated with preterm delivery and a high perinatal mortality rate. Conclusions: Early recognition of the severity of infection and prompt management by a multidisciplinary team of intensivists, anesthetists, neonatologists, obstetrician, midwives are the key to success. Vigilant infection control measures must be strictly practiced during all pregnancy events.